Fatores Associados à Realização de Cesárea em Primíparas com uma Cesárea Anterior Factors Associated with Cesarean Section in Primipara Women with One Previous Cesarean Section - José Guilherme Cecatti; Carla Betina Andreucci; Pilar Souza Cacheira; Helaine Maria Besteti Pires; João Luiz Pinto e Silva; Márcia Maria Auxiliadora de Aquino (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2000)
Objetivo: avaliar a via de parto em um grupo de gestantes primíparas de baixa renda com uma cesárea anterior e os fatores associados à repetição da cesárea no segundo parto. Pacientes e Métodos: realizou-se um estudo caso-controle com 356 gestantes atendidas de janeiro de 1993 a janeiro de 1996 na Maternidade do CAISM/UNICAMP. Constituíram os casos as 153 gestantes que tiveram o segundo parto por cesárea, e os controles, as 203 que tiveram o segundo parto vaginal. Para a análise utilizaram-se médias, desvio padrão, teste t de Student, teste de Mann-Whitney, chi² e "odds ratio" (OR) e IC 95% para cada possível fator associado à realização de cesárea no segundo parto. Resultados: a via do segundo parto foi vaginal em 57% das vezes. Dentre as diversas variáveis estudadas, as que mostraram estar significativamente associadas à realização de cesárea no segundo parto foram: maior idade materna (para mulheres com 35 anos ou mais, OR = 16,4), antecedente de abortamento (OR = 2,09), indução do trabalho de parto (OR = 3,83), rotura prematura de membranas (OR = 2 ,83), a não-realização de analgesia durante o período de dilatação (OR = 5,3), o diagnóstico de algum sinal de vitalidade fetal alterada (OR = 2,7) e a ocorrência do parto à tarde (OR = 1,92). Conclusões: os resultados indicam que os fatores associados à repetição de cesárea em mulheres com uma cicatriz de cesárea nesta população são predominantemente médicos, mas há a possibilidade de se proporem intervenções dirigidas a diminuir o índice de repetição de cesáreas. Purpose: to evaluate the route of delivery in a group of low-income primipara pregnant women with a previous cesarean section, and the factors associated with the repetition of the cesarean section on the second delivery. Patients and Methods: it was a case-control study including 356 women who were assisted at the Maternity of CAISM/UNICAMP during the period between January 1993 and January 1996. The cases were 153 women whose second delivery was through a cesarean section and the controls were 203 women whose second delivery was vaginal. For analysis, means, standard deviation, Student's t-test, Mann-Whitney test, chi² test and odds ratio (OR) with 95% CI for each factor possibly associated with cesarean section on the second delivery were used. Results: the route of the second delivery was vaginal for 57% of the women. Among the several variables studied, those which showed to be significantly associated with a cesarean section on the second delivery were: higher maternal age (for women over 35 years, OR = 16.4), previous abortions (OR = 2.09), induced labor (OR = 3,83), premature rupture of membranes (OR = 2.83), not having an epidural analgesia performed during labor (OR = 5.3), the finding of some alteration in fetal well-being (OR = 2.7) and the delivery occurring during the afternoon (OR = 1.92). Conclusions: these results indicate that the factors associated with the repetition of cesarean section in women with a previous scar of cesarean section in this population are predominantly medical; however, there is still the possibility of proposing interventions directed to decreasing the rates of repeated cesarean sections.